The Effect of Interactive Digital News Mapping Media on News Text Writing Skills - Bindu Ria Magdalena Sihombing; Beslina Afriani Siagian; Vina Merina Br Sianipar (Raja Zulkarnain Education Foundation, 2026)
This study aims to determine: 1) the news text writing skills of class XII-AP students of SMK Pariwisata Imelda Medan before using interactive digital news mapping media; 2) the news text writing skills of class XII-AP students of SMK Pariwisata Imelda Medan after using interactive digital news mapping media; 3) the effect of using interactive digital news mapping media on news text writing skills. The research approach applied in this study is a quantitative approach through a quasi-experimental design with a one-group pretest-posttest design. This approach and design were used to determine the effect of using interactive digital news mapping media on news text writing skills. The population of this study was class XII-AP students of SMK Pariwisata Imelda Medan who participated in pretest activities for news text reading skills and participated in learning news text writing skills using interactive digital news mapping media. The sample used in this study was 30 students taken using a purposive sampling technique. Data on news text writing skills were collected using a news text writing skills test instrument. Data on news text writing skills were analyzed using a paired sample t-test. The results of the study showed that the mean news text writing skills of class XII-AP students of SMK Pariwisata Imelda Medan before using interactive digital news mapping media was 10.73 (53.67). The mean news text writing skills of class XII-AP students of SMK Pariwisata Imelda Medan after using interactive digital news mapping media was 15.73 (78.67). The paired sample t value was -8.403 at sig. 0.00. Thus, sig. 0.000 <0.05 so that Ho was rejected and Hi was accepted, meaning that there was a significant influence of the use of interactive digital news mapping media on the news text writing skills of class XII-AP students of SMK Pariwisata Imelda Medan in the 2025/2026 academic year.